Celsior® vs. St Thomas® cardioplegia: analysis of myocardial protection and clinical safety in neonates - Bulescu, Nicolae Cristian; Mitchell, Julia; Metton, Olivier; El Jonhy, Naoual; Amaz, Camille; Perouse de Montclos, Thomas; Lilot, Marc; Mewton, Nathan; Henaine, Roland (Frontiers in Pediatrics, 2024)
Objective: To compare the effectiveness and safety of Celsior® crystalloid solution to St Thomas® solution as cardioplegia in pediatric arterial switch surgery.: A retrospective study was conducted on 180 patients who underwent arterial switch operation (ASO) between 2005 and 2019. The patients were divided into two groups: the St Thomas group receiving St Thomas solution and the Celsior® group receiving Celsior® solution. The study aimed to assess myocardial protection while evaluating clinical outcomes of patients between groups.Results: Baseline characteristics not different between groups. The postoperative troponin release trends and blood lactate levels were not different between groups. However, the Celsior® group had a significant lower incidence of delayed sternal closure (9,7% vs 19,5%; p=0,09) and mechanical circulatory support (ECMO)(4,9% vs 24,7%; p<0,001) compared to the St Thomas group. The length of stay in the intensive care unit (ICU) was significantly shorter in the Celsior® group (4.6 ± 3.36 days vs 8.72 ± 5.08 days, respectively; p<0.001).There was no significant difference in 30-day mortality between the two groups (2,9% vs 2,6%; p=0,147).The study suggests that Celsior® solution is effective and safe for myocardial protection in pediatric arterial switch surgery. It may offer potential benefits such as reduced need for delayed sternal closure and ECMO support, as well as shorter ICU stay. However, the study has limitations including its retrospective design and the use of different cardioplegic solutions during different time periods. Further prospective randomized trials are needed for confirmation.